A Projection of Land Needed for Settlements and Conversion of Paddy Fields in Solok City - Ricky, Ricky; Rustiadi, Ernan; Barus, Baba (The ITB Journal Publisher, 2017)
Abstract. The city of Solok, despite being a growing urban area, cannot entirely abandon its agricultural sector due to its influence on the development of the region and its contribution to maintaining national food security. The development of settlement in the city of Solok needs to consider the existing paddy fields while avoiding unnecessary conversion, which should be a last resort. Infrastructure development should not be directed to the existing and potential paddy fields, since, generally, settlement development prefers these areas. This study aimed to estimate the land needed for settlements based on population projections, the assessment of land suitability for paddy field by a spatial analysis and a simulation of land use change considering infrastructure as driving factor. The methods used in this study are the Saturation Model, Spatial Analysis, Markov Chain and Cellular Automata (CA) Analysis. The results demonstrate that: (1) the estimated population in 2031 using the saturation model will be 71,524 inhabitants, which would require 223.08 Ha of settlements; (2) the existing paddy fields cover 971.27 Ha, some parts were categorized unsuitable due to its slope but this was overcome by the construction of terraces; and (3) the Markov Chain and CA analysis predicted over 150 Ha of paddy field conversion in Solok by 2024. The road development plan in Solok City tends to follow the market trend directed at the existing and potential paddy field areas. The study predicts a significant loss of paddy fields, especially in areas with a high suitability class.Keywords. Paddy Fields Conversion, Land Use Change, Saturation Model, Land Suitability, CA Markov.Abstrak. Walaupun secara administratif berstatus sebagai sebuah kota, Kota Solok tidak dapat begitu saja meninggalkan sektor pertanian karena masih kuatnya pengaruh sektor tersebut dalam pembangunan wilayah dan adanya kepentingan mempertahakan ketahanan nasional. Pembangunan permukiman di Kota Solok perlu memperhatikan eksistensi lahan sawah yang ada dan sebisa mungkin menghindari alih fungsi yang tidak seharusnya dan harus benar-benar sesuai kebutuhan. Pengembangan infrastruktur permukiman sebaiknya tidak diarahkan pada lokasi-lokasi sawah eksisting dan lahan-lahan yang potensial untuk sawah. Namun pengembangan permukiman pada umumnya lebih memilih untuk mengalih fungsi lahan sawah yang ada dan potensial. Penelitian ini bertujuan 1) memperkirakan kebutuhan lahan untuk kawasan permukiman berdasarakan proyeksi pertumbuhan penduduk 2) analisis kesesuaian lahan untuk komoditas padi sawah dan 3) mensimulasikan perubahan penggunaan lahan dengan mempertimbangkan infrastruktur sebagai faktor yang berpengaruh. Metoda yang digunakan adalah Model Saturasi, Analisis Spasial, Markov Chain dan Cellular Automata (CA). Hasil penelitian ini menunjukkan bahwa: 1) Perkiraan populasi penduduk kota Solok dengan model saturasi pada tahun 2031 mencapai 71.524 jiwa yang akan membutuhkan lahan seluas 223,08 Ha untuk kawasan permukiman 2) Luas lahan sawah aktual sebanyak 971,27 Ha, sebagian terkategorikan tidak sesuai karena faktor lereng, namun faktor penghambat tersebut telah diatasi dengan pembangunan terasering 3) Diperkirakan akan terjadi pengurangan luas lahan sawah lebih dari 150 Ha pada tahun 2024. Rencana perluasan jaringan jalan di Kota Solok terbukti cenderung mengikuti trend pasar yang diarahkan pada lokasi sawah-sawah eksisting dan potensial, alih fungsi lahan sawah diperkirakan tetap akan terjadi dalam jumlah yang cukup tinggi terutama pada lahan-lahan berkesesuaian baik.Kata kunci. Konversi Lahan Sawah, Model Kejenuhan, Perubahan Penggunaan lahan, Kesesuaian Lahan, CA Markov.